Tingkat Kejadian Kecacingan pada Sapi Potong di Peternakan Rakyat Kecamatan Seputih Raman - A A Candra; A N Hasanah; Z Zairiful (Politeknik Negeri Lampung, 2023)
Factors that influence the success of a cattle breeding business are seeds, feed and health management in the form of disease control. The disease that often occurs in cattle is helminthiasis. This research was to analyze an incidence of helminthiasis in beef cattle. The research used an observation method. Data collection was done by taking all fecal samples from 391 beef cattle in Seputih Raman sub-district. A fecal samples examination checked with Mc. Master and Sedimentation test at Veterinary Laboratory of Lampung. The results indicated that the incidence rate of helminthiasis in beef cattle at smallholder farms in Seputih Raman sub-district was about 45,27%. The highest incidence found in Rama Dewa village is about 84,00%. Helminths specie found in beef cattle at smallholder farm in Seputih Raman sub-district are from Nematode class (Haemonchus sp. is 3,3%, Trichostrogylus sp is 1,5%, Mecistocirus sp. is 2,3%, Trichuris sp.is 0,5% and Oesophagostomum sp. is 6,6%), Trematode class (Paramphistomum sp is 28,1% and Fasciola sp. is 14,8% and Cestode class (Hymonlepis spp. Is 0,5% and Moniezia sp. is 2,0%. The highest incidence was found in Paramphistomum sp species about 28,1%. The highest incidence rate of helminthiasis in beef cattle at smallholder farms in Seputih Raman sub district, ranging from 100-2200 eggs.The highest of worm eggs of the Cestode genus is foundin the Moniezia sp. species ranging from 100-2.200 eggs.